2020
DOI: 10.22271/tpr.2020.v7.i3.079
|View full text |Cite
|
Sign up to set email alerts
|

Studies on growth and yield characters of chickpea (Cicer arietinum L.) varieties suitable for mechanical harvesting

Abstract: The growth and yield characters of chickpea varieties suitable for mechanical harvesting were evaluated through field experiment conducted for three consecutive years (2016__17 to 2018__19) during rabi season on vertisols under rainfed conditions at Regional Agricultural Research Station, Nandyal, Andhra Pradesh. The investigation was carried out in split plot design with three replications. Two plant geometries (30.0 × 10.0 cm and 22.5 × 10.0 cm) were assigned to main plots and six chickpea varieties (viz., G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 0 publications
3
3
0
Order By: Relevance
“…and minimum of 32.02% was shown by the untreated control (T0) respectively. These results were in conformity with the earlier research findings of [8].…”
Section: Harvest Index (%)supporting
confidence: 93%
See 1 more Smart Citation
“…and minimum of 32.02% was shown by the untreated control (T0) respectively. These results were in conformity with the earlier research findings of [8].…”
Section: Harvest Index (%)supporting
confidence: 93%
“…took 70.67 days for the same. Similar trends for days to 50% flowering were found by earlier research works of [8].…”
Section: Days To 50% Floweringsupporting
confidence: 90%
“…The lowest pod height was also formed at a higher height from the soil surface in tall plants. In chickpeas, the lowest pod height is usually between 15 and 20 cm (Basha et al, 2018). Lack of access to cultivars with the appropriate lowest pod height, especially in developing countries, is considered as one of the most important reasons for a decrease in the cultivated area of chickpea in the world in a way that increasing chickpea production in developed countries such as Australia, Canada, and the United States is mostly contributed to mechanized harvesting (Basha et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Despite the small seed weight, the plants were taller (73.22 cm) (Table 5). Mechanical harvesting of chickpeas has a severe problem because of the crop height and header loss in combined harvesting (Basha et al, 2020).…”
Section: Cluster Analysismentioning
confidence: 99%
“…Principal component analysis (PCA) can transform several possibly correlated variables into a smaller number of variables in a group called principal components . Through cluster analysis (CA), the genotypes are grouped based on complex traits rather than one character (Brown-Guedira et al, 2000). Past studies revealed the clustering of 17 chickpea genotypes from different geographical origins, seed colors, and grain yields into eight groups (Dani and Murty, 1985).…”
Section: Introductionmentioning
confidence: 99%